Placental Extracts, Proteins, and Hydrolyzed Proteins as Active Ingredients in Cosmetic Preparations for Hair Loss: A Systematic Review of Available Clinical Evidence - Ewelina Szendzielorz; Radoslaw Spiewak (Applied Sciences)
Placentae and their derivatives have been used in both traditional and modern medicine, as well as in cosmetic sciences. Although hair loss is frequently mentioned among problems for which the placenta is supposed to be a remedy, the evidence seems rather scarce. The aim of this study was to highlight the clinical evidence for the efficacy of placenta products against baldness and hair loss. Methods: This systematic review was performed according to PRISMA and PICO guidelines. Database searches were conducted in PubMed, Google Scholar and Scopus. Results: Among the 2922 articles retrieved by the query, only 3 previously published clinical trials on placental products were identified. One study was a randomized controlled trial, in which the efficacy of a bovine placenta hair tonic was found to be comparable to that of minoxidil 2% in women with androgenic alopecia. Another controlled study showed that a porcine placenta extract significantly accelerated the regrowth of shaved hair in healthy people. The third study was an uncontrolled trial of a hair shampoo and tonic containing equine placental growth factor in women with postpartum telogen effluvium with unclear and difficult-to-interpret results. Due to the design and methodology of these studies, the level of evidence as assessed with the GRADE method was low for the first study and very low for the other two. Conclusions: The very limited scientific evidence available to date appears, overall, to indicate the efficacy of placental products in both inhibiting hair loss and stimulating hair growth. Unfortunately, the number of clinical studies published to date is very limited. Further, carefully designed, randomized controlled trials of well-defined placental products are needed to definitively address the question of the value of the placenta and its derivatives in hair loss.